Mapping the Current Research Agenda on Scholarly Publishing: Scopus-Indexed Reviews - Elena Tikhonova; Lilia Raitskaya (National Research University Higher School of Economics, 2020)
Nearly ten years ago, scholarly publishing came to the fore in research on scientific communication spurred by the evolving Open Science system, the reinvention of peer reviews, and new attitudes to scholarly publications in the ranking-based academic environment. Here, the JLE editors revisit the field of scholarly publishing and identify the most popular areas where potential JLE authors might have difficulty. In this editorial, Scopus-indexed reviews are analysed to map the prevailing trends. The editorial review shows that the trends include open access, peer review transparency, the changing role of libraries in scholarly publishing, CrossRef's initiatives, outsourcing and skills lacking in publishing, the impact of universities' prescribed lists for publishing research, open-access monographs, and the role of commercial publishers.